Evaluación del Modelo Estándar de Control Interno (MECI) y desarrollo de un modelo diferencial para el nivel territorial en Colombia (2014)
This research aims to establish the difficulties presented by local authorities in the municipalities of 3rd to 6th category in implementing the Standard Model of Internal Control -MECI, considering that this model is the tool that allows the development of Internal Control Policy in Colombia and constitutes the foundation for achieving the institutions objectives. Based on the diagnosis aspects to improve or adjust this model are determined, in order to correct its implementation and in the medium term these entities can improve their corporate governance. The research takes concepts of the New Public Management (NPM); from this approach is observed and analyzed aspects related to good governance and the vocation for public service by state officials, the mechanisms for democratization of public administration and finally the basic principles of social responsibility. The research is applied and used as a model methodology CIPP (contextinput-process-products) so that the results, analysis and recommendations are shown through four stages or levels. The main findings and conclusions point to confirm the hypothesis; flaws in the implementation of the model were determined due to methodological aspects on which improvement or adjustment points are generated.